2009
DOI: 10.1021/jp907772c
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Studies of Methanol Decomposition on Subnanometer Pd Clusters

Abstract: A density functional theory study of the decomposition of methanol on subnanometer palladium clusters (primarily Pd 4 ) is presented. Methanol dehydrogenation through C-H bond breaking to form hydroxymethyl (CH 2 OH) as the initial step, followed by steps involving formation of hydroxymethylene (CHOH), formyl (CHO), and carbon monoxide (CO), is found to be the most favorable reaction pathway. A competing dehydrogenation pathway with O-H bond breaking as the first step, followed by formation of methoxy (CH 3 O)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
65
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(77 citation statements)
references
References 62 publications
8
65
0
2
Order By: Relevance
“…Previously, the reaction mechanisms of CH 3 OH dissociation with the C-H, O-H, or C-O bond on the surfaces have been investigated theoretically and experimentally [6,[9][10][11][12][13]. In the present work, we perform only the configuration of site A as initial state (IS A ) to calculate mechanism for CH 3 OH dissociation on 2Cu/ZnO (1010) [25], CuCl(111) [1], and Au(111) [4] surfaces.…”
Section: Methanol Dissociationmentioning
confidence: 99%
See 3 more Smart Citations
“…Previously, the reaction mechanisms of CH 3 OH dissociation with the C-H, O-H, or C-O bond on the surfaces have been investigated theoretically and experimentally [6,[9][10][11][12][13]. In the present work, we perform only the configuration of site A as initial state (IS A ) to calculate mechanism for CH 3 OH dissociation on 2Cu/ZnO (1010) [25], CuCl(111) [1], and Au(111) [4] surfaces.…”
Section: Methanol Dissociationmentioning
confidence: 99%
“…Many previous experiment and calculation investigations of CH 3 OH dissociation on the surfaces suggested that the O-H scission was proposed as the initial dissociation step [4,10], C-H scission was more favorable than O-H scission [11,12], and the C-O scission suggested to be impossible one for both experimental and theoretical studies [9,11,[13][14][15]. However, CH 3 OH dissociation through three routes of bond scission on 2Cu/ZnO   0 1 10 surface in this present works is not still found.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[80,81] Theoretischen Voraussagen zufolge ist auch die Methanoloxidation auf subnanometergroßen Palladiumclustern energetisch dann günstiger, wenn die Reaktion mit einer C-H-statt mit einer O-H-Bindungsspaltung beginnt. [82] Im Laufe der letzten drei Jahrzehnte wurden viele Gasphasenexperimenten zur mechanistischen Untersuchung der CH 3 OH!CH 2 [86] Beispiele von Gasphasenexperimenten, in denen die Oxidation von Methanol eindeutig mit der Aktivierung einer C-H-Bindung beginnt, sind eher selten. Die Reaktion von Mn(CO) 3 À mit Methanol stellt eine dieser Ausnahmen dar, bei der im ersten Schritt eine C-H-Bindungsaktivierung des Substrats stattfindet; dieser Schritt ist auch geschwindigkeitsbestimmend.…”
Section: Der Erste Schritt: Spaltung Der Starken O-h-oder Der Schwächunclassified